2020
DOI: 10.3389/fonc.2020.570933
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Plus Chemotherapy Is Associated With Improved Survival Compared to Radiotherapy Alone in Patients With Primary Vaginal Carcinoma: A Retrospective SEER Study

Abstract: BackgroundThe efficacy of radiotherapy plus chemotherapy (RTCT) versus radiotherapy alone (RT) in the treatment of primary vaginal carcinoma has been controversial. We aimed to evaluate the up-to-date efficacy of RTCT on primary vaginal carcinoma in a real-world cohort.MethodsWe performed a retrospective analysis in patients with primary vaginal carcinoma retrieved from the Surveillance, Epidemiology, and End Results Program database from 2004 to 2016. Kaplan–Meier survival curves were plotted and compared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(36 reference statements)
3
2
0
Order By: Relevance
“…This study confirmed that older age and larger tumor size were negatively associated with survival, consistent with other studies (4,11,12,(37)(38)(39). We also found that a higher tumor stage was negatively correlated with the survival of VC patients, similar to previous studies (4,17,(38)(39)(40).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study confirmed that older age and larger tumor size were negatively associated with survival, consistent with other studies (4,11,12,(37)(38)(39). We also found that a higher tumor stage was negatively correlated with the survival of VC patients, similar to previous studies (4,17,(38)(39)(40).…”
Section: Discussionsupporting
confidence: 93%
“…This study confirmed that older age and larger tumor size were negatively associated with survival, consistent with other studies (4,11,12,(37)(38)(39). We also found that a higher tumor stage was negatively correlated with the survival of VC patients, similar to previous studies (4,17,(38)(39)(40). Instead of using a single FIGO or AJCC stage, we investigated T, N, and M stages in our models because they show a more elaborate representation of tumor progress than a single stage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Rajagopalan et al 29 and Samant et al 30 reported that concurrent chemoradiation is independently prognostic of improved survival in patients with vaginal cancer. Zhou et al 31 indicated that concurrent chemoradiation is preferrable to radiotherapy alone for patients with vaginal adenocarcinoma with tumor size less than 2 cm, and FIGO Stage I. Radiotherapy (EBRT plus brachytherapy) combined with surgery is one of the currently recommended treatments for vaginal cancer. 8,12 We found that the OS of the radiotherapy combined with surgery group was significantly better than the OS of the other two groups (both P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment strategies are often adapted from evidence in locally advanced cervical cancer due to the lack of sufficient clinical evidence. When surgery is not an option, the organ-sparing treatment plan relies on definitive radiotherapy,6 which includes external beam radiotherapy targeting the primary tumor and regional lymph nodes and a boost to the residual tumor with brachytherapy,9 together with concurrent chemotherapy 8 10…”
Section: Introductionmentioning
confidence: 99%